A metal–organic framework-derived Zn1−xCdxS/CdS heterojunction for efficient visible light-driven photocatalytic hydrogen production. Issue 18 (22nd April 2021) - Bai, Tianyu; Shi, Xiaofan; Liu, Ming; Huang, Hui; Yu, Mei-Hui; Zhang, Jijie; Bu, Xian-He
Abstract : The zeolitic imidazolate framework-8 (ZIF-8) was used as a precursor to prepare ZnCdS-based quantum dot heterojunctions to achieve the visible light-driven water splitting hydrogen production efficiently. Abstract : ZCS-C (ZnCdS/CdS) QDs were synthesized via low-temperature vulcanization using zeolitic imidazolate framework-8 (ZIF-8) nanoparticles as a precursor, cation exchange, and heterojunction construction. Without any precious metal as a cocatalyst, the photocatalytic hydrogen production rate of ZCS-C-3 QDs reached 2.7 mmol g −1 h −1 under visible light irradiation. The optimized sample exhibited an outstanding chemical stability and recyclability, which is superior to most of the reported Zn1− x Cd x S-based photocatalysts.